The Influence of Competence and Motivation on Employee Performance at PT PLN (Persero) ULP Tanjung Karang - Dwi Khafifah; Toton (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The purpose of this study is to investigate the impact of ability and motivation on the performance of employees of PT PLN (Persero) ULP Tanjung Karang. It will be the main source of task success to improve labor productivity. The survey respondents were all employees of PT PLN (PERSERO) ULP Tanjung Karang, totaling 30 people. Data were collected and analyzed using multiple linear regression equations using SPSS version 25. The coefficient of determination for the test results was 0.417. The current study found that both competence and motivation have significant positive effects on employee performance, with f-test scores at the significant level of 0.000.